Intra‐rater reliability of leg blood flow during dynamic exercise using Doppler ultrasound. Issue 19 (7th October 2021) - Amin, Sachin B.; Mugele, Hendrik; Dobler, Florian E.; Marume, Kyohei; Moore, Jonathan P.; Lawley, Justin S.
Abstract: Developing an exercise model that resembles a traditional form of aerobic exercise and facilitates a complete simultaneous assessment of multiple parameters within the oxygen cascade is critically for understanding exercise intolerances in diseased populations. Measurement of muscle blood flow is a crucial component of such a model and previous studies have used invasive procedures to determine blood flow kinetics; however, this may not be appropriate in certain populations. Furthermore, current models utilizing Doppler ultrasound use isolated limb exercise and while these studies have provided useful data, the exercise model does not mimic the whole‐body physiological response to continuous dynamic exercise. Therefore, we aimed to measure common femoral artery blood flow using Doppler ultrasound during continuous dynamic stepping exercise performed at three independent workloads to assess the within day and between‐day reliability for such an exercise modality. We report a within‐session coefficient of variation of 5.8% from three combined workloads and a between‐day coefficient of variation of 12.7%. These values demonstrate acceptable measurement accuracy and support our intention of utilizing this noninvasive exercise model for an integrative assessment of the whole‐body physiological response to exercise in a range of populations. Abstract : We demonstrated that muscle blood flow could be reliably measured within and between days to acceptable standards using Doppler ultrasound at three different workloads during continuous dynamic stepping exercise. Such a model, combined with assessment of multiple parameters within the oxygen cascade facilitates a complete integrative approach for determining exercise intolerance in multiple populations.